PENGEMBANGAN VIDEO PEMBELAJARANiKEWIRAUSAHAAN UNTUK MAHASISWAiPENDIDIKAN EKONOMIiFKIPiUNIVERSITAS TANJUNGPURAiPONTIANAK - Genoveva Sonia; Husni Syahrudin; Muhammad Basri (Universitas Tanjungpura, 2021)
AbstractThisistudyiaimsito develop and determine the feasibility of entrepreneurship learning video for Economic Education student, FacultyiofiTeacheriandiEducation, Tanjungpura University Pontianak. The development of videos is based on the methods used by teachers who still often use the lecture method, especially when there is a COVID-19 pandemic, the intensity of learning is online, so that students feel bored with this learning method. In addition, students' lack of understanding of some materials in entrepreneurship courses underlies the researchers to develop this entrepreneurship learning video. Theiresearch methodiusediisitheiR&D method, with the ADDIE developmentistage model, (1)iAnalysis (2) Designi(3)iDevelopment (4) Implementation (5) Evaluation. Data collection techniques in this study were validation sheets, questionnaires, and also the results of the pre-test and post-test. The resultsiofithisistudy indicate that (1) the product has gone through the product manufacturing process, product validation, and field trials; (2) The results of the validation by material experts obtained a value of 3.85 with a